2018
DOI: 10.1016/j.ctrv.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of action of eribulin mesylate: Emerging data and clinical implications

Abstract: Eribulin mesylate (eribulin) is a synthetic analogue of the marine-sponge natural product halichondrin B. Eribulin exhibits potent antiproliferative activities against a variety of human cancer cell types in vitro and in vivo, and is used for the treatment of certain patients with advanced breast cancer or liposarcoma who are refractory to other treatments. The antiproliferative effects of eribulin have long been attributed to its antimitotic activities. Unlike other microtubule-targeting agents, eribulin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 64 publications
0
57
0
10
Order By: Relevance
“…Although no significant difference in OS was observed between groups with high and low ALC (c; p = 0.287), those with NLR ≥5.0 had significantly worse OS than those with NLR < 5.0 (d; p < 0.001). antitumor immunity [7,8], while the number of tumorinfiltrating lymphocytes has been known to affect the efficacy of eribulin treatment for breast cancer [23]. Given the difficulty in determining the number of tumor-infiltrating lymphocytes in daily practice, we propose the use of ALC as a predictive marker of the efficacy of eribulin, considering that a significant correlation between tumor-infiltrating lymphocytes and ALC has been already confirmed [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no significant difference in OS was observed between groups with high and low ALC (c; p = 0.287), those with NLR ≥5.0 had significantly worse OS than those with NLR < 5.0 (d; p < 0.001). antitumor immunity [7,8], while the number of tumorinfiltrating lymphocytes has been known to affect the efficacy of eribulin treatment for breast cancer [23]. Given the difficulty in determining the number of tumor-infiltrating lymphocytes in daily practice, we propose the use of ALC as a predictive marker of the efficacy of eribulin, considering that a significant correlation between tumor-infiltrating lymphocytes and ALC has been already confirmed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Eribulin is currently in the spotlight for its multiple modes of action [7]. Preclinical studies have shown that, besides inhibiting microtubule growth, eribulin exerts biological effects on the immune system through the suppression of the epithelial-mesenchymal transition, vascular remodeling, and tumor microenvironment improvement [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study patients received Eribulin monotherapy independently of the HR status. Eribulin has multiple modes of action underlying its antiproliferative effect in cancer cells and survival benefit in clinical trials [34]. It is best known for its inhibitory effect on microtubule polymerization, thereby interfering with microtubule dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In two prospective, randomized phase III trials, the non-taxane microtubule inhibitor eribulin mesylate was associated with significantly longer OS, or with a trend towards longer OS, when compared to C or other treatments of physician choice, despite the lack of significant benefit in terms of PFS [12,25]. Potential mechanisms to explain these clinical data consist in eribulin's ability to revert epithelial-to-mesenchymal transition (EMT) and metastatic spread of breast cancer cells [26], to enhance immune system activation [27] or to remodel tumor vasculature [28,29]. Since there are no published preclinical data supporting these mechanistic explanations in the case of CV, in this study we preliminarily explored the hypothesis that CV reshapes systemic immune system activation.…”
Section: Discussionmentioning
confidence: 99%